2022
DOI: 10.1016/j.aninu.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of carcass traits, meat quality, and serum metabolome between Shaziling and Yorkshire pigs

Abstract: This study aims to compare the meat quality of Shaziling and Yorkshire pigs and to find the potential indicator in serum for superior meat quality. Six Shaziling and Yorkshire pigs at 30, 60, 90, 150, 210, and 300 d of age were selected to examine carcass traits, meat quality, and serum metabolome. The results showed that the body weight, carcass length, and loin eye area of Shaziling pigs at 150, 210, and 300 d of age were significantly lower than those of Yorkshire pigs ( P < 0.05). Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…This result signifies that PHF at 750 gm/ton feed effectively replaces 1,500 gm SCC in the broiler ration and exhibits a similar SCC performance as reflected by EPI. Calderano et al [ 10 ], Khose et al [ 16 ], and Khosravinia et al [ 32 ] showed an improvement in survivability, feed efficiency, and body weight when a natural source of choline was used to substitute synthetic choline in bird diets, and this agrees with our study findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result signifies that PHF at 750 gm/ton feed effectively replaces 1,500 gm SCC in the broiler ration and exhibits a similar SCC performance as reflected by EPI. Calderano et al [ 10 ], Khose et al [ 16 ], and Khosravinia et al [ 32 ] showed an improvement in survivability, feed efficiency, and body weight when a natural source of choline was used to substitute synthetic choline in bird diets, and this agrees with our study findings.…”
Section: Discussionsupporting
confidence: 92%
“…Diets enriched with L-carnitine reduce the fat accumulation in adipose tissue by enhancing fatty acid oxidation [ 15 ]. In addition, it has already been demonstrated that higher serum LC levels could be correlated with better meat quality in pigs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insertion frequency was different between two types of pig and dominant for LEPROT -SINE-RIP in Chinese native breeds and LEPR -SINE-RIP in commercial pigs. Several studies have indicated that compared to commercial pigs, native pigs showed a slower growth rate, thicker backfat, and low lean percentage [ 39 , 40 , 41 , 42 , 43 ]. Natural selection and genetic drift are also powerful forces shaping the distribution and accumulation of retrotransposons [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distance from the anterior margin of the symphysis pubis to the fovea of the first cervical spine on the left half of the carcass was measured as carcass length (cm). Backfat thickness (mm) and loin eye area (height × width × 0.7 cm 2 ) were measured between the 6th and 7th ribs using vernier caliper [ 5 ]. The lean/fat percentage was calculated as the percentage of lean/fat weight to carcass weight, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Non-Chinese commercial breeds and native Chinese pig breeds display distinctive differences in terms of meat quality, prolificacy, and growth. Specifically, native Chinese pig breeds have better meat quality (such as the cherry-red color, high levels of marbling, soft texture and superior flavor), lower growth rates, and lower lean meat rates when compared with non-Chinese commercial breeds [ 4 , 5 , 6 ]. With the improvement in people’s living standards, a growing demand for healthier, tastier, and more nutritious pork has emerged.…”
Section: Introductionmentioning
confidence: 99%